Pengembangan Media Pembelajaran Interaktif Berbasis Power Point pada Materi Kosa Kata Bahasa Arab - Kafa Thoyyibah, Alif; Rosikh, Fahrur; Abidah, Zakiyatul; Mustofa, Muhamad Arif (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2025)
Learning media has an important role in the teaching and learning process, but in reality there are still many learning activities that do not utilize the media optimally. Based on the results of field research, it was found that Arabic language learning at MI Islamiyah Kedungmegaraih Kembangbahu Lamongan did not find interactive learning media and student learning outcomes in mastering Arabic vocabulary were still low. This study aims to develop a power point learning media on vocabulary material and to determine the feasibility and effectiveness of the developed power point learning media. This study was conducted using the Research and Development (R&D) method which adopted the development of Borg & Gall. The instrument for data collection used questionnaires and interviews. Based on the results of this study, it was found that the development of interactive media based on power point includes three main things, namely: media, material and language. in aspects: 1) media feasibility is 97.2% in the